FACTORS INFLUENCING STRESS AMONG SENIOR HIGH SCHOOL STUDENTS AT BESTLINK COLLEGE OF THE PHILIPPINES - BULACAN (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
Stress is an inherent aspect of student life, significantly influencing academic performance, mental health, and overall well-being. Understanding the causes of stress, effective coping mechanisms, and their impact on student performance is crucial for fostering a supportive educational environment. Common Causes of Student Stress:  Academic Pressure: The demand to excel in studies, meet deadlines, and prepare for examinations can be overwhelming, leading to heightened stress levels. ​  Future Concerns: Worries about career prospects and meeting parental expectations contribute significantly to student stress. ​  Social Challenges: Navigating interpersonal relationships and societal pressures can add to the emotional burden experienced by students.​  Lifestyle Factors: Poor diet, lack of exercise, and inadequate sleep can exacerbate stress, affecting both physical and mental health. ​  Effective Coping Strategies:  Time Management: Implementing structured schedules and prioritizing tasks can help manage academic responsibilities efficiently. ​  Physical Activity: Engaging in regular exercise has been shown to reduce stress levels and improve mood. ​  Social Support: Maintaining connections with friends, family, and support networks provides emotional stability and a sense of belonging.​  Relaxation Techniques: Practices such as meditation, deep breathing, and mindfulness can alleviate stress and enhance focus. ​ nhs.uk  Healthy Lifestyle Choices: Adopting a balanced diet, ensuring adequate sleep, and limiting stimulants like caffeine can positively influence stress levels. ​  Impact on Academic Performance:  Chronic stress can impair concentration, memory, and decision-making abilities, leading to a decline in academic performance. Addressing stress through effective coping strategies not only enhances mental health but also improves learning outcomes and overall student success. ​  By recognizing the signs of stress and implementing appropriate coping mechanisms, students can better navigate academic challenges, leading to improved performance and a healthier, more balanced lifestyle. This research employed a descriptive survey methodology to collect and analyze data. A survey questionnaire was administered to twenty-five (25) randomly selected Senior High School students from Bestlink College of the Philippines – Bulacan, located in San Jose del Monte, Bulacan. To ensure accessibility and convenience, the questionnaire was distributed via Google Forms. A four-point Likert scale was utilized to assess the intensity of respondents' opinions, with options ranging from "Strongly Agree" to "Strongly Disagree." This scale effectively captures the degree of agreement or disagreement with specific statements, providing valuable insights into student perspectives.​ The study's findings indicate that students experience significant pressure from various sources, potentially contributing to elevated stress levels. Parental expectations were rated as "Very High" with a weighted mean of 3.37, academic requirements as "High" with a mean of 3.06, peer relationships as "High" with a mean of 2.93, and self-expectations as "High" with a mean of 3.05.​  These results align with existing research highlighting the impact of parental expectations on student stress. Studies have shown that high parental expectations can lead to increased academic stress, which may affect students' well-being and academic performance. ​  Additionally, academic stress has been associated with test anxiety, with parental expectations playing a moderating role. This underscores the complex interplay between external pressures and students' emotional responses. ​  The significant pressure from various sources, including parents, academic requirements, and personal expectations, can contribute to increased stress levels among students. Addressing these stressors is crucial for promoting students' mental health and academic success. Establishing a supportive learning environment is essential for promoting students' mental health and academic success. Implementing effective strategies to reduce academic pressure and encourage healthy coping mechanisms can significantly enhance students' well-being and performance.​  Strategies to Alleviate Academic Stress and Promote Coping:  Foster Open Communication: Encouraging open dialogue among students, educators, and parents helps identify stressors and collaboratively develop solutions, ensuring students feel heard and supported.  Set Realistic Goals: Assisting students in establishing achievable academic and personal goals prevents feelings of overwhelm and promotes a sense of accomplishment.  Integrate Coping Skills into the Curriculum: Incorporating programs like the FRIENDS Resilience Program equips students with tools to manage stress, build resilience, and navigate challenges effectively.  Provide Mental Health Resources: Ensuring access to counseling services and mental health support within educational settings allows students to seek help when needed, contributing to a nurturing atmosphere.  Encourage Extracurricular Activities: Promoting participation in activities beyond academics helps students develop diverse skills, build friendships, and find outlets for stress relief.  Offer Faculty Training: Training educators to recognize signs of stress and anxiety enables them to provide timely support and refer students to appropriate resources.  Create a Positive Physical Environment: Designing classrooms and common areas that are welcoming and comfortable can reduce stress and enhance focus and engagement.  By implementing these strategies, educational institutions can cultivate an environment that prioritizes mental health alongside academic achievement, fostering holistic development and well-being among students.
Keywords: academic stress; stressors; coping strategies; student well-being; mental health; educational environment; resilience; peer relationships; parental expectations; academic performance.